Forward to AIDS 2014: Now is the Time to Unite for the Global HIV/AIDS Epidemic - Gregory Pappas, MD, PhD (Global Health and Education Projects, Inc., 2014)
As AIDS activists, advocates, researchers, practitioners, scientists, and policy makers from around the world prepare for the forthcoming 20th International AIDS Conference (AIDS 2014) which takes place from 20-25 July in Melbourne, Australia, Gregory Pappas, MD, PhD, former Executive Director of the Washington DC's local Host Committee, International AIDS Society (IAS) organizing committee member, and Director, HIV/AIDS Program in the District of Columbia, Washington, DC, USA, reflects, for the first time, on his experiences hosting the world conference and bringing AIDS conference to United States after 22 years. He shares some of the key challenges and opportunities confronting program planners, policy makers and advocates in the efforts to address the global epidemic.